Studi Sosiologi Sastra dalam Novel Hujan Bulan Juni Karya Sapardi Djoko Damono (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the use of imagery and images in the poems of Sapardi Djoko Damono through a structural approach. Using qualitative methods and Ferdinand de Saussure's structuralism theory, the research focuses on the linguistic structures that form visual, auditory, and kinesthetic imagery in Sapardi's works. The imagery in his poems functions as a medium to present images, sounds, and movements that evoke emotional and intellectual responses from readers. In this analysis, every word and phrase is examined as a sign consisting of the signifier and the signified, which together form rich poetic imagery. The findings indicate that Sapardi meticulously utilizes linguistic structures to create imagery that not only depicts the beauty of nature and everyday life but also conveys nuances of emotions such as solitude, longing, and love. This structural approach enables a deeper understanding of how imagery in Sapardi's poems communicates emotional and symbolic meanings, creating an intuitive and profound reading experience for the audience. This research is expected to contribute to the study of Indonesian poetry and enrich literary analysis perspectives through the structuralism approach.